The impact of epidemics on green innovation: global analysis - Zhao, Xin-Xin; Ma, Jie; Wen, Jun; Chang, Chun-Ping (Technological and Economic Development of Economy, 2024)
Epidemics and their resulting pandemics have become essential factors influencing economic development, financial stability, poverty, and ultimately a country’s innovation level, including green technology innovation. This research thus investigates epidemic events’ correlation to green innovation by operating with skewed panel data involving 134 countries from 1971 to 2018 and provides compelling proof that Epidemics have a detrimental effect on green innovation, not only for the current year but also for the next six years. We also show that the quality of institutions and financial development levels weaken epidemics’ detrimental effects on green innovation. Overall, the findings would draw particular attention from policymakers.First published online 17 April 2023